Pengaruh Thin Capitalization dan Capital Intensity terhadap Tax Avoidance - Fauziah, Latifa; Helmy, Herlina (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to determine the effect of Thin Capitalization and Capital Intensity on tax avoidance. This study is a type of quantitative research and uses panel data regression analysis with the help of Eviews 12. This study uses four proxies to measure tax avoidance variable, namely Lon-Run Effective Tax Rate (LRETR1, LRETR2) and Book Tax Differences (BTAX1, BTAX2. The thin capitalization variable is measured using the ratio Maximum Allowable Debt (MAD) and the capital intensity variable measured using the ratio between total fixed assets by total assets. The study population was manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. The study sample was determined by purposive sampling method, so that 58 sample of manufacturing companies were obtained. Based on panel data regression analysis, the result show that thin capitalization has an effect on tax avoidance with LRETR2, BTAX1, BTAX2 measurements, but the LRETR1 measurements has no effect. While capital intensity has no effect on tax avoidance with the four proxies, namely LRETR1, LRETR2, BTAX1, BTAX2 measurements.